2021
DOI: 10.3390/ma14154227
|View full text |Cite
|
Sign up to set email alerts
|

Silver Decorated βTCP-Poly(3hydroxybutyrate) Scaffolds for Bone Tissue Engineering

Abstract: Implantations in orthopedics are associated with a high risk of bacterial infections in the surgery area. Therefore, biomaterials containing antibacterial agents, such as antibiotics, bactericidal ions or nanoparticles have been intensively investigated. In this work, silver decorated β tricalcium phosphate (βTCP)-based porous scaffolds were obtained and coated with a biopolymer—poly(3-hydroxybutyrate)-P(3HB). To the best of our knowledge, studies using silver-doped βTCP and P(3HB), as a component in ceramic-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Thus, Ag 3 PO 4 -modified CAp HC scaffolds can perfectly prevent bacterial infection and regenerate bone defects. Notably, HC-0.1 showed antibacterial activity even though the Ag content (9.9 × 10 –4 wt %) was remarkably lower than those in other reported scaffolds (0.08–20 wt %), ,,,,, and the antibacterial activity of the reported scaffolds was quite weak when the Ag content was <1 wt %. , This superiority of HC-0.1 seems to be due to its honeycomb framework structure because bacteria and necrotic bone were eliminated from the CAp HC scaffolds without Ag 3 PO 4 modification (HC-0) through their channels. This suggests that a honeycomb structure that possesses uniaxial channels perfectly penetrating the scaffold is inherently appropriate for the prevention of bacterial adhesion and growth.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Thus, Ag 3 PO 4 -modified CAp HC scaffolds can perfectly prevent bacterial infection and regenerate bone defects. Notably, HC-0.1 showed antibacterial activity even though the Ag content (9.9 × 10 –4 wt %) was remarkably lower than those in other reported scaffolds (0.08–20 wt %), ,,,,, and the antibacterial activity of the reported scaffolds was quite weak when the Ag content was <1 wt %. , This superiority of HC-0.1 seems to be due to its honeycomb framework structure because bacteria and necrotic bone were eliminated from the CAp HC scaffolds without Ag 3 PO 4 modification (HC-0) through their channels. This suggests that a honeycomb structure that possesses uniaxial channels perfectly penetrating the scaffold is inherently appropriate for the prevention of bacterial adhesion and growth.…”
Section: Discussionmentioning
confidence: 92%
“…As described above, a surface modification technique is necessary to localize the intended amount of antibacterial substances on both the outer and pore surfaces of the scaffold framework. In previous studies, antibacterial bioceramic scaffolds were fabricated by compacting and sintering precursors containing antibacterial ions, such as zinc, copper, magnesium, and silver. ,, However, in the abovementioned method, most antibacterial ions were present within the material framework rather than on the surface. Therefore, after preparation of the scaffold framework, an effective method to selectively replace a portion of apatite on the framework surface with antibacterial compounds is considered necessary for achieving both bone regeneration and infection prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Poly(3-hydroxybutyrate) (P(3HB)) was produced by bacterial fermentation from glycerol (Orlen Południe S.A., Trzebinia, Poland) in the presence of NaCl (Chempur, Piekary Śląskie, Poland) at 45 °C using bacterial strain Zobellella denitrificans (Wilhelms-Universität Münster, Münster, Germany), as described previously [ 59 ]. The biomass after fermentation was lyophilized and then extracted with chloroform (Chempur, Piekary Śląskie, Poland).…”
Section: Methodsmentioning
confidence: 99%
“…230 Similarly, in vivo bone-repair evaluation showed that after the PHBV/HA scaffold was implanted into the tibia of rabbits, osteoblasts appeared at the interface region of the implant material and tissue, leading to a thickness increase of the nascent bone from 130 to 770 μm within months, accompanied by scaffold degradation. 132 In addition to HA, other components can also improve the mechanical properties and osteogenic cell activity of PHA devices, such as tricalcium phosphate (TCP), 104,181,240,[245][246][247] bioactive glass (BG), 86,162,174,181,186,244,248 B-wollastonite, 249,250 graphene oxide (GO), 251,252 natural coral, 253 carbon nanotubes (CNTs), [254][255][256] CaCO 3 , 257 montmorillonite (MMT), 258 bredigite (BR), 259,260 and diatom shells (DSs). 261 Moreover, some polymers such as PVA, 262 PEG, 154,263,264 PCL, 134,175,252,261,265 chitosan (CS), 183,234,266 collagen (Col), 182 and silk fibroin (SF), 233,267 and new materials (e.g., polyaniline (PANi), 251 aloe vera gel, 268 starch, 26...…”
Section: Biomaterials Science Reviewmentioning
confidence: 99%
“…In addition to bone repair, tissue inflammation can be reduced if the PHA composite has antimicrobial activities. Ag ions, 245 ZnO, 184 and cinnamaldehyde (CIN) 162 are proven to exert antibacterial effects in bone tissue engineering grafts.…”
Section: Phas For Medical Applicationsmentioning
confidence: 99%